The Institute of the Commissioner for Human Rights: history, modernity, prospects - Issabekova, V.S. (Bulletin of the Karaganda University “Law Series”, 2024)
The article is devoted to the study of topical issues of functioning of the institution of the Ombudsman for Human Rights in the context of its historical development from the moment of its creation to the modern period. The scientific research reveals historical prerequisites for the emergence and peculiarities of the formation of the institution of the Ombudsman in the territory of Kazakhstan. Its role and essence from the position of different points of view of scientists is revealed. The author conducts a detailed analysis of the modern period of activity of the Ombudsman, paying special attention to the transformation of the institution and strengthening of its significant positions in the legal field of our statehood. The purpose of this article is a historical study of the development of the institution of the Commissioner for Human Rights in the Republic of Kazakhstan and foreign countries, its modern interpretation and prospects for its further development. To reveal the purpose of scientific research, various methods of scientific cognition were used, mainly: historical, comparative-legal, empirical. As a result of the study, the author identified the main stages of development of the institution of the Commissioner for the Protection of Human Rights. Positive trends in the development of the institution of the Ombudsman are outlined. Recommendations aimed at rationalization of the national legislation of the Republic of Kazakhstan, with the purpose of further prospects of strengthening the effectiveness of the Commissioner for Human Rights and its human rights functions are given.